Makna Isteri Yang Cakap - Rumiyati Rumiyati (Jurnal Teologi dan Pelayanan Kerusso, 2017)
God only created two types of people, men, and women. There is no third type. And the existence of both of them is to complement each other. So to unite the two God formed an institution called family. That's where they will unite as husband and wife. They have their respective roles. The existence of a wife is a helper for her husband. And this is where a wife of noble character is needed to be a helper. What is a wife of noble character? Through the exposition of the book of Proverbs 31: 10-31 it will answer. A wife of noble character is a wife who has all the parts of a respectable character, and an extraordinary power to carry out all her duties and obligations, especially in her household, she is able to make a decision that can be useful for herself and her entire family.